Public Sector Discount Rates: A Comparison of Alternative Approaches - John Creedy; Hemant Passi (New Zealand Government, The Treasury, 2017)
This paper sets out the alternative approaches to the public sector discount rate and explains the assumptions involved. There are two main ways of thinking about the discount rate. First, the social opportunity cost of capital approach (SOC) defines the discount rate as the rate of return that a decision-maker could earn on a hypothetical `next best alternative' to a public investment. Second, the social rate of time preference approach (SRTP) defines the discount rate as the rate of return that a decision-maker requires in order to divert resources from use in the present, to a public investment. In an `ideal' market, these two rates are brought into alignment in equilibrium. However, as there are no markets for public investments, there are no market signals to equate preferences for investing in such projects with rates of return. There is no completely objective way of determining public sector discount rates. Essentially the discount rate reflects how the government values the future when making decisions on behalf of society: value judgements and assumptions are necessary. The paper aims to clarify these judgements. Elements of both approaches may be relevant to many policy and operational decisions that require discounting, in which case different approaches may be relevant for different contexts. The paper also briefly considers the use of hyperbolic discounting.
Keywords: H43; H50; 330; Public sector discount rate; social opportunity cost; social time preference rate; Öffentlicher Sektor; Opportunitätskosten; Kapitalkosten; Diskontierung; Zeitkonsistenz; Theorie